2022
DOI: 10.1063/5.0079902
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the thermoelastic component of the photoacoustic signal of silicon membranes coated with a thin TiO2 film

Abstract: The reduction of the photogenerated charge carriers' influence in periodically illuminated thin silicon membranes is investigated by using the experimental setup of an open photoacoustic cell in the standard range of modulation frequencies from 20 Hz to 20 kHz. It is confirmed that the deposition of a 200 nm thin film of titanium dioxide on the 30- and 50  μm silicon membrane leads to a large increase of the thermoelastic component of the photoacoustic signal, which restores the flexibility lost to the membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…Figures 4(a The value obtained from the classical model of f c3 = 4kHz was much lower than expected from the literature, around f c3 = 10kHz. Also, the damping factor δ c3 was expected to be around 0.6 [23,52]. Similar results of simulation for A400 sample are presented in Fig.…”
supporting
confidence: 78%
“…Figures 4(a The value obtained from the classical model of f c3 = 4kHz was much lower than expected from the literature, around f c3 = 10kHz. Also, the damping factor δ c3 was expected to be around 0.6 [23,52]. Similar results of simulation for A400 sample are presented in Fig.…”
supporting
confidence: 78%
“…The plasmaelastic bending was ultimately disregarded due to the likelihood of short minority lifetimes (τ ) within the thin MEMS structures, greatly reducing the excess carrier density. Comparing thermal effects and plasmaelastic effects, previous works [39,40] suggested that plasmaelastic effects would only be relevant at high frequencies. Beyond this, the plasmaelastic bending in silicon often causes a shift in the output phase when going from sub-bandgap to superbandgap [41,42].…”
Section: A1 Plasmaelastic Bendingmentioning
confidence: 99%